Differences between Indonesia and Singapore based on PISA 2015: Five-factor students’ perception in science education - Janu Arlinwibowo; Hanif Cahyo Adi Kistoro; Heri Retnawati; Gulzhaina Kuralbayevna Kassymova; Bagdaulet Kenzhalyevich Kenzhaliyev (Jurnal Inovasi Pendidikan IPA, 2020)
As a neighbouring country whose location is very close, there is a unique fact where the results of the PISA study show very different results between Indonesia and Singapore. Students' perceptions of learning have an important role to detect the quality of learning. Thus, this study aims to determine the factors of student perception of natural science learning and the differences between the two countries based on these factors. The sample in this study were 5870 Indonesian students and 5272 Singaporean students who took the 2015 PISA survey. The research data were the results of the PISA survey (codes ST098, ST100, ST103, and ST104) regarding student perception of natural science learning. The data analysis technique used is Principal Component Analysis to detect factors and Discriminant Analysis to show differences between the two countries. Students' perceptions of science learning in Singapore and Indonesia can be classified into five factors: Practicum, Assistant, Explorative, Counseling, and Collaborative. Based on these factors, there are differences in the perception of the implementation of science learning between Indonesian and Singaporean students. Indonesian students tend to be stronger in defining that science learning is full of exploration, collaboration, and teachers play the role of counselor very well, while Singapore students feel more than practical learning based on science and teachers provide student assistance in dealing with difficulties in the learning process.